OPTIMIZING SYSTEM INFORMATION DESIGN FOR HOSPITALIZED USING COMBINATION OF DFD – ERD AND USER INTERFACE - Br Kembaren, Suci; Praptiningsih, Yulia Eka; Warmansyah, Julio; Nurâ€™ainingsih, Dyah (Jurnal Ilmiah Informatika Komputer, 2008)
In the information era, competence and skill in processing data into ready to use information becomes necessary. Special hospital for pregnancy care and as a center for inpatient of giving birth mother require specific information system for handling patient data. The main problem in a hospital is the difficulty of medical doctor and medical staff in using computer as a media for entering data or creating reports. Conventional approach of classic database development is using DFD – ERD. To overcome problems when using this approach, taking into account user interface may enrich the design process. In this case study, impact of the approach for the developed system using DFD – ERD only compared to the same system with user interface. The fact shows that the user interface enriched approach provides operational easiness. Keyword(s): Information system, Hospital, InpatientSubject Description : D.2.Software Engineering | D.2.10.Design | Methodologies